Fingolimod ameliorates axonal damage in experimental autoimmune encephalomyelitis. Issue 3 (25th June 2014) - Jin, Shijie; Takeuchi, Hideyuki; Horiuchi, Hiroshi; Wang, Yue; Kawanokuchi, Jun; Mizuno, Tetsuya; Suzumura, Akio
Abstract Objectives Fingolimod (FTY) is a new oral drug for multiple sclerosis. It acts as a functional antagonist for sphingosine 1‐phosphate receptor (S1PR). After phosphorylateion by sphingosine kinase in vivo, FTY binds to S1PR on lymphocytes to downregulate S1PR, thereby preventing lymphocyte egress from lymphoid tissues to reduce infiltration of autoreactive lymphocytes into the central nervous system. FTY easily passes through the blood–brain barrier and directly affects cells in the central nervous system. Recently, we have shown that FTY exerts neuroprotective effects by suppressing pro‐inflammatory functions of glial cells and by upregulating neuroprotective functions of neuronal and glial cells in vitro. In the present study, we examined whether FTY exerts neuroprotective effects in vivo in the chronic phase of experimental autoimmune encephalomyelitis (EAE). Methods Myelin oligodendrocyte glycoprotein‐induced EAE mice were orally treated with FTY (1 mg/kg/day) or vehicle (water) once a day starting at the disease peak (15 days after immunization). To evaluate gliosis and axonal damage, the lumbar spinal cords were examined immunohistochemically at 28 days after immunization. Results FTY treatment starting at disease peak improved the severity of symptoms, and reduced gliosis and axonal damage in the spinal cord, as assessed by glial staining and formation of neuritic bead/spheroid. Conclusions FTY exerts protective effects on axonal impairments during the chronic phase of EAE. The neuroprotective effect of FTY could synergistically suppress pathology of multiple sclerosis with its immunosuppressive effect.